Can cutaneous sarcoid be a marker for metabolic syndrome? A case illustration - Rochelle Cheryl Monteiro; Suvidha D Kamath; Jacintha Martis (Wolters Kluwer Medknow Publications, 2023)
Sarcoidosis is a multisystem inflammatory disorder involving the organs such as lungs, lymph nodes, and eyes. Cutaneous involvement is seen in 20%-35% of the cases with systemic involvement. We report the case of a 46-year-old female, who presented with multiple skin-colored papules and nodules over the body, with no evidence of systemic involvement. On further investigation she was detected to have diabetes mellitus and metabolic syndrome (MetS). The association of MetS with systemic sarcoidosis has been described in the literature. However, there is no previous reported association of isolated cutaneous sarcoidosis with MetS. In our context, the presence of MetS was an incidental finding. Hence, cutaneous sarcoid should be considered a marker for underlying MetS and all cases of isolated cutaneous sarcoid should be extensively investigated for the same, even in the absence of systemic manifestations. We illustrate this case as this association is hitherto unreported.